Presencia del Vencejo Montañés Aeronautes montivagus en la Argentina - Moschione, Flavio N. (1993)
Presence of the White-tipped Swift (Aeronautes montivagus) in Parque Nacional Calilegua, Jujuy province, becomes fírst record for Argentina.